2020
DOI: 10.1371/journal.pone.0238998
|View full text |Cite
|
Sign up to set email alerts
|

Retention of E. coli and water on the skin after liquid contact

Abstract: The frequent contact people have with liquids containing pathogenic microorganisms provides opportunities for disease transmission. In this work, we quantified the transfer of bacteria—using E . coli as a model- from liquid to skin, estimated liquid retention on the skin after different contact activities (hand immersion, wet-cloth and wet-surface contact), and estimated liquid transfer following hand-to-mouth contacts. The results of our study show that the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, there is still an uncertainty in this result as the adsorption rate of S. aureus to skin is still not available. The E. coli adsorption rate found by Pitol [ 49 ] was used instead as the adsorption rate for S. aureus . The uncertainty comes from the differences between the two bacteria, as E. coli is a Gram-negative bacteria, and S. aureus is a Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is still an uncertainty in this result as the adsorption rate of S. aureus to skin is still not available. The E. coli adsorption rate found by Pitol [ 49 ] was used instead as the adsorption rate for S. aureus . The uncertainty comes from the differences between the two bacteria, as E. coli is a Gram-negative bacteria, and S. aureus is a Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The uncertainty comes from the differences between the two bacteria, as E. coli is a Gram-negative bacteria, and S. aureus is a Gram-positive bacteria. It has been observed that there is a difference of transfer efficiencies between Gram-positive and Gram-negative bacteria to skin [ 49 ]. Therefore, future study on the adsorption rate of S. aureus to skin is needed to get a more certain result.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anaerobic bacterium, Bacteroides fragilis, presented the average of 1.2×1010, followed by the Bacteroides spp with 9.9×109 and the Peptococcus spp with 6.9×109. As for the analysis of the number of microorganisms per gram of tissue, according to the malign colorectal neoplasic condition, the main aerobic bacterium was the Escherichia coli, which presented the average of 2.7×10 10 , followed by the Staphylococcus epidermidis with 2.6×10 10 and the Klebsiella spp with 2.2×10 10 . The aerobic bacterium Bacteroides spp, presented the average of 2.5×10 10 , followed by the Peptococcus spp with 1.8×10 10 and the Bacteroides fragilis with the average of 6.8×10 9 , according to what was described by Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the quantity of pathogens retained on the skin after liquid contact is a function of both the volume of liquid on the skin and the concentration of the agent in the liquid. Exogenous factors such as temperature, humidity or the use of topical products have an impact on the hydration of the skin, and skin hydration could potentially infl uence water retention [10], fact that can be transposed to the fecal content that is in frequent contact with the cutaneous surface.…”
Section: Resultsmentioning
confidence: 99%